Handbook of exchange rates - James, Jessica, 1968-; Marsh, Ian W., 1966-; Sarno, Lucio (Wiley handbooks in financial engineering and econometrics ;, 2012)
"Handbook of Exchange Rates is an impressive compilation of research from more than thirty-five leading researchers and experts on the topic. The book is clearly organized into five succinct sections that explore the foreign exchange (FX) market, from its background and economic foundation to current practices, obstacles, and policies in the modern foreign exchange market. Part I presents an overview of the history of the FX market and exchange rate regimes, the key instruments/players in the FX trading environment, and both macro and micro approaches to FX determination. Next, Part II focuses on forecasting exchange rates, featuring methodological contributions on the sstatistical methods for evaluating forecast performance, parity relationships, fair value models, and flow-based models. Part III treats FX as an asset class, outlining active currency management, currency hedging, hedge accounting, high frequency and algorithmic trading in FX, and FX strategy-based products. Part IV discusses products and pricing in FX, the FX options market, and volatility derivatives. Finally, the book concludes with a section on FX markets and policy, prediction and management of FX crises, FX regimes and policy; regulation in FX market that also features discussion of the effects of exchange rate regime choice on international trade. Each chapter follows the same easy-to-follow format. Following an introduction, a description of theory is presented along with key formulae. Next, the discussed theory is applied to a real data set and accompanied with illustrative descriptions. Exercises and real-world examples from the finance industry are spread throughout each chapter, and a summary provides a brief overview of main points and concepts"--